Design of Android-Based Learning Media “MathArt” on Simple Interest, Discounts, and Taxation at the Lower Secondary Level of Education - Lestary, Ratnah; Apriani, Mulya Sarti; Kesuma, Rizki Putri; Cahyo, Riko Dwi; Siagian, Teddy Alfra (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to design and evaluate the effectiveness of the MathArt application, an Android-based learning media focused on simple interest, taxes, and discounts for lower secondary education at SMPN 17 Bengkulu City. The research adopts a four-stage Research and Development (R&D) method: 1) research, 2) planning, 3) development, and 4) product trials. Data were collected qualitatively via Google Forms, targeting data form students and teachers. Questionnaires assessed MathArt’s practically and effectiveness. Responses showed strong positive reception on MathArt, with 87.32% from students and 87.54% from teachers. This indicates its high suitability as a social arithmetic learning resource.